Satisfaction as a Mediator and Its Interaction With Adherence to Labor Analgesia Protocols: A Cross-Sectional Survey of Chinese Medical Personnel - Lang, Dong; Long, Chengxu; Lin, Shuna; Xie, Yinghua; Chen, Fangfei; Zhao, Rui; Liu, Chunping; Tang, Shangfeng (Frontiers in Public Health, 2022)
Background: Although the Chinese promotion of labour analgesia began in 2018 to improve maternal health, high-quality medical care is difficult to provide to pregnant women when medical staff cannot implement standard labour analgesia procedures. This study aims to examine medical personnel's adherence to labour analgesia protocols and to explore the relationships among adherence, satisfaction, and other factors. Methods: The data were from a national cross-sectional dataset (N = 13,944) of the 2020 Chinese Labour Analgesia Pilot Evaluation Project. Mediating and moderating effects analyses were used to examine the role of satisfaction as a mediator between support measures and adherence. Results: There were differences in adherence between different types of medical personnel. Support measures and satisfaction had a positive association with adherence to labour analgesia protocols. Satisfaction had a significant mediating and moderating effect on the relationship between support measures and adherence to labour analgesia standards. Moderating effects of professional titles and attitudes were also observed. Conclusion: Primary health care policies worth considering include comprehensive incentives for medical institutions to improve the use of labour analgesia by medical personnel. It is also worth considering providing more training opportunities for the staff in anaesthesiology departments.